Dantrolene: In Doxorubicin Toxicity - EMIN BUYUKOKUROGLU, MEHMET; TAYSI, SEYITHAN; BUYUKAVCI, MUSTAFA; MEMISOGULLARI, RAMAZAN; OZABACIGIL, FATMA; BAKAN, EBUBEKIR (Asian Journal of Chemistry, 2010)
Doxorubicin (DOX) is a widely used anthracycline in the treatment of hematological and solid tumors. However, there are serious toxic effects on cardiovascular and hematopoietic system, which limits the use of the drug. This study examines the effect of dantrolene (5 and 10 mg kg-1) on DOX (20 mg kg-1, i.p.)-induced cardiotoxicity and hematotoxicity in normal rats. Change in nitric oxide (NO•) levels in cardiac tissue were measured and hemoglobin (Hb), white blood cells (WBC), red blood cells (RBC) and platelets were counted with an automatic counter. Pretreatment of rats with 5 and 10 mg kg-1 doses of dantrolene, markedly reduced the NO• levels in the cardiac tissue. The hematotoxicity was characterized by leukopenia and thrombocytopenia that appeared after 48 h of single dose DOX (20 mg kg-1) administration. Dantrolene (5 and 10 mg kg-1) 0.5 h before doxorubicin injection ameliorated the hematotoxicity induced by doxorubicin. These results showed that dantrolene has provided a protective effect against DOX-induced nitrosative stress in the heart and hematotoxicity.